2020
DOI: 10.1101/2020.08.07.241075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specification and epigenetic resetting of the pig germline exhibit conservation with the human lineage

Abstract: SummaryInvestigations on the human germline and programming are challenging due to limited access to embryonic material. However, the pig as a model may provide insight on transcriptional network and epigenetic reprogramming applicable to both species. Here we show that during the pre- and early migratory stages pig primordial germ cells (PGCs) initiate large-scale epigenetic reprogramming, including DNA demethylation involving TET-mediated hydroxylation and potentially base excision repair (BER). There is als… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 86 publications
(138 reference statements)
0
13
1
Order By: Relevance
“…Recent work from our laboratories has shown the developmental correspondence between human and pig germ cells during the initial period of gastrulation (Kobayashi et al, 2017;Zhu et al, 2021). We propose that building on these investigations into pig gastrulation using singlecell -omics and gene manipulation will offer new knowledge on the mechanisms of meso-endoderm and ectoderm specification with relevance to understanding human development.…”
Section: Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent work from our laboratories has shown the developmental correspondence between human and pig germ cells during the initial period of gastrulation (Kobayashi et al, 2017;Zhu et al, 2021). We propose that building on these investigations into pig gastrulation using singlecell -omics and gene manipulation will offer new knowledge on the mechanisms of meso-endoderm and ectoderm specification with relevance to understanding human development.…”
Section: Reviewmentioning
confidence: 95%
“…Notably, pig PGCs are first found in the posterior epiblast expressing SOX17, BLIMP1, and TFAP2C, and the cluster expands to about 120 cells by induction of proliferating PGC-competent progenitors upon exposure to BMP. These newly formed pig PGCs (pPGCs) pause their proliferation briefly, only to resume cell-cycle progression after they start their migration (Kobayashi et al, 2017;Zhu et al, 2021). The PGCs originating in the amnion of Cynomolgus monkey appear to be in a proliferative phase soon after specification (Sasaki et al, 2016), but how PGCs migrate to posterior epiblast against the movement of amnion that expands toward the opposite direction merits further investigations.…”
Section: Origin Of the Germline In Mammalsmentioning
confidence: 99%
“…More recently, it has been shown that PRDM14 mediates the removal of H3K27me3 marks from the Xi during XCR in PGCs [ 143 ]. In addition, a recent study in pig showed that Xist is silenced in most pre-migratory PGCs [ 144 ]. XCR begins in pre/early migrating PGCs and continues in gonadal PGCs.…”
Section: Xcr During Mouse Developmentmentioning
confidence: 99%
“…XCR begins in pre/early migrating PGCs and continues in gonadal PGCs. The kinetics of XCR is not explained by distance of genes to the Xic [ 144 ]. In summary, XCR takes places during epigenetic reprogramming of the germline and is linked to the expression of pluripotency genes, including transcription factors.…”
Section: Xcr During Mouse Developmentmentioning
confidence: 99%
See 1 more Smart Citation